Causes and Consequences of Economic Centrality: Evidence from Canadian Proviinces - Sandé, Linda Manuella (Université d'Ottawa | University of Ottawa, 2014)
In this paper, I employ a network approach to examine regional economic integration in Canada. To do so, I study both the causes and consequences of economic centrality of Canadian provinces. Firstly, I estimate the exogenous determinants of economic centrality. I find that geographic centrality and land area have positive effects on economic centrality. Secondly, I analyze the consequences of economic centrality on Canadian provinces using panel data. I test for the impact of economic centrality on three dependent variables, namely the gross domestic product (GDP) per capita, education and life expectancy. The results show that economic centrality positively affects each of these outcomes, demonstrating that economic networking has a positive effect on welfare.